Failure response of rocks under different cyclic loading histories - Taheri, Abbas; Shirani Faradonbeh, Roohollah (2023)
The post-failure instability of rocks was investigated through an extensive experimental study under four different loading histories, including the monotonic quasi-static loading, single-level systematic cyclic loading (SLSCL), multi-level systematic cyclic loading (MLSCL), and post-peak cyclic loading (PPCL). The lateral strain-controlled and double-criteria damage-controlled testing methodologies were implemented for the experiment. A combined postpeak Class I-II behavior to different extents was detected for soft to strong rocks, while the unstable fracture propagation was more dominant for stronger rocks under monotonic loading. Additionally, rocks exhibited more self-sustaining behavior under MLSCL history with increasing the number of cycles before the failure point. On the other hand, the results of the SLSCL tests revealed that rock brittleness reaches its maximum value by applying systematic cyclic loadings at stress levels close to the monotonic strength. However, the effect of post-peak cyclic loading (PPCL) history on the post-failure response of rocks was negligible.